Older people presenting to the emergency department after a fall: a population with substantial recurrent healthcare use. Issue 9 (1st October 2011) - Close, Jacqueline C T; Lord, Stephen R; Antonova, Evgeniya (Jenya); Martin, Monique; Lensberg, Benedikte; Taylor, Morag; Hallen, Jamie; Kelly, Ann
Abstract : Objectives: To document patient characteristics, care pathways, healthcare use and costs of fall-related emergency department (ED) presentations by older adults. Participants and methods: All fallers aged ≥70 years, presenting to the ED of a 450-bed metropolitan university hospital in Sydney, Australia (1 April 2007 through 31 March 2009) were studied. Data were collected from the ED electronic information system, ED clinical records and the hospital electronic information system database. Population estimates for 2008 for the local areas served by the hospital were used to estimate ED presentation rates. Results: Of 18 902 all-cause ED presentations, 3220 (17.0%) were due to a fall. Among fallers, 35.4% had one or more ED presentations and 20.3% had had one or more hospital admissions in the preceding 12 months. Fall-related ED presentation led directly to hospital admission in 42.7% of the cases, the majority of which (78.0%) received acute care only (length of stay—14.4 days for men and 13.7 days for women) and the remaining cases underwent further inpatient rehabilitation (length of stay 35.6 days for men and 30.1 days for women). After hospitalisation, 9.5% of patients became first-time residents of long-term care facilities. All fall-related ED presentations and hospitalisations cost a total of A$11 241 387 over the study period. Conclusions: Older fallers presenting to the ED consume significant healthcare resources and are an easily identifiable high-risk population. They may benefit from systematic fall-risk assessment and tailored fall-prevention interventions.